Letter-writing and Transnational Activism on Behalf of Indonesian Political Prisoners: Gatot Lestario and his Legacy - Hearman, Vannessa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
Amnesty International estimated in 1977 that between 600,000 and 750,000 Indonesians had been or were still imprisoned as a result of the Army-led anti-communist violence in Indonesia in the mid-1960s. This article charts the relationship between members of Amnesty International and the Religious Society of Friends (Quakers) with a political prisoner on death row in East Java, Gatot Lestario, a former leader of the Indonesian Communist Party. This article draws on the letters he wrote over a period of three years before his execution in 1985 and interviews with his pen pals. It traces the ways in which he encouraged his pen pals to advocate for human rights in Indonesia and their responses, as well as his own involvement in political prisoner advocacy. This case study illustrates the disappearance of Indonesia's previously close and solidary relationship with the socialist world and its replacement at the people-to-people level with human rights activism involving Western activists. This is particularly evident in the increasingly important role played by members of Amnesty International, the Quakers and other overseas organizations concerned with Indonesia. Finally, the article assesses Gatot Lestario's impact, after his execution, on the development of a long-term advocacy network for Indonesia's political prisoners.